Standing Tall - Odeven, E. (Swimming Technique, 2003)
Although short in stature, Japan's Kosuke Kitajima, blessed with extraordinary technique, is a giant among breaststrokers. Size doesn't always matter. But elite male swimmers, such as Australian Ian Thorpe and American Michael Phelps, are usually big, strong fellows. Kosuke Kitajima is an exception to the rule. The skinny, 5-foot-8 3/4-inch Japanese native is a world-class swimmer who relies more on skill than size. This is described in this article.